Analysis of Cr (VI) accumulation from feed to broiler chicken by using spectroscopy (Asian Journal of Medical and Biological Research, 2022)
Broiler chicken is one of the major dietary protein sources in Bangladesh. This study is aimed to investigate the status of chromium (VI) content in broiler feeds and water, as well as the risk of chromium (VI) in broiler meat, liver, and brain. For this investigation, a total of five broiler-rearing farms were chosen, each with a different type of broiler feed. A total of fifteen broiler chickens along with the water and feed samples were collected from those broiler farms. The concentration of chromium (VI) in feed, water, broiler meat, liver, and brain samples was determined using an Atomic Absorption Spectrophotometer (AAS). Two feed samples (Farm B and Farm D) were found to be chromium (VI) polluted (3.157±0.050 mg/Kg and 3.510±0.095 mg/Kg respectively), while water samples were found to be devoid of contamination. Only meat, liver, and brain samples from several farms were found to have chromium (VI). Brain samples exhibited the highest concentration of chromium (3.550±1.281 mg/Kg) compared to the liver (2.700±1.084 mg/Kg) and muscle meat (0.857±0.076 mg/Kg) samples. The amounts of chromium (VI) in the broiler brain and liver were found to be substantially higher than FAO and WHO acceptable standards. The rate of chromium (VI) concentration in meat samples was below the allowed level. It is proposed that precautions should be taken to detect chromium in chicken feed to assess health hazards and protect humans from food that could have serious negative consequences for their health.Asian J. Med. Biol. Res. 2022, 8 (4), 225-229